La Notion de qualité télévisuelle dans la production fictionnelle britannique (Cinéma & Cie. Film and Media Studies Journal, 2012)
This essay explores the notion of Quality TV, as it has been applied to British TV fiction. The quality of British TV fiction has often been associated with teleplays, adaptations and the movement of social realism. Through a study of TV productions, of the discourses of scholars and critics, and a comparison with the concept of American Quality TV, this article highlights some of the relevant criteria of Quality TV in the UK, most notably the educational, ethical or realist dimension of the programs and their visual sobriety. This particular definition of quality can be explained in part by the original public service mandate of the TV industry in the UK, similar to most European countries. The article ends with a study of contemporary discourses about Quality TV in the UK. Nowadays, there seems to be an important tension between a traditional conception of Quality TV and a newer one, which is more in line with the American model and is usually associated to cinematic and expensive TV series. This short study of fictional Quality TV underlines the evolutionary nature of the concept of quality and raises questions about the future of TV production in the United Kingdom.